(untitled) (Research, Society and Development, 2023)
Introduction: It is known that spina bifida represents a congenital malformation that leads to impairments in sensorimotor development, predisposing the infant to needing physiotherapy from birth. Objective: to seek evidence from scientific studies on the role of physiotherapy in children with spina bifida. Methodology: this is a systematic literature review research. The research sources were obtained through a bibliographic survey, using articles published in the following databases: Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Publications (PubMed/Medline), and Google Scholar. Results and discussion: the studies found that physiotherapy contributes to the learning of motor skills, locomotion, postural adjustments, greater functional independence, through kinesiotherapy, neuromuscular stimulation, proprioceptive neuromuscular facilitation, among others. Conclusion: through physiotherapy, these children will develop new sensorimotor skills, prevent muscle shortening and complications secondary to spina bifida, stimulating the child’s entire neuropsychomotor development.